Grain Corridor Agreement and Turkey’s Role in the Russia-Ukraine War - Hakkı M. Ay; Adnan Söylemez (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2023)
On the morning of February 24, 2022, when the Russian military entered Ukraine and launched air and missile raids on the targets it detected in the depths of this country, a war started in the east of Europe. As a result of the war between two of the world’s largest grain producers, a global grain crisis is taking place. Turkey has long sought to emphasize connectivity and strengthen its strategic position at the intercontinental crossroads between Europe and Asia. Functionally, Turkey serves as a vital transit corridor for key resources such as energy and food supplies, which becomes even more important given the economic and trade disruptions of Russia’s war in Ukraine. This study analyzed Turkey’s diplomatic efforts and policies during the war and the food deal process.